Dry matter accumulation in genotypes of bean submitted to different levels of nitrogen Acúmulo de massa seca em genótipos de feijoeiro submetidos a diferentes níveis de nitrogênio - Juliano Ribeiro Araújo; Magno Antonio Patto Ramalho; Adriano Teodoro Bruzi; Ângela de Fátima Barbosa Abreu (Ciência e Agrotecnologia, 2009)
The objective of this study was to verify the response of dry matter accumulation in bean lines (Phaseolus vulgaris L.) to different levels of nitrogen fertilizers. Six genotypes ('BRSMG Majestoso', 'Pérola', MA-I-18.13, 'Ouro Negro', 'BRSMG Talismã', and MA-I-2.5) were evaluated in Lavras, testing three N levels (0, 60, and 120 kg/ha) and using ammonium sulphate as N source. The experimental design adopted was the randomized block design in a 6 x 3 factorial structure with three replications and the plots were composed of five 5-m rows. The seeds were sown in November 2005 and July 2006. Total dry mass of five competitive plants was evaluated after 35 days from sowing, harvested from a pre-determined place in the useful area of the plots. This process was repeated every ten days until the harvest. The grain yield was also evaluated in one of the rows of the useful area of the plots. It was observed that regarding the dry mass accumulation, the genotypes did not present different responses at the N levels and the average increase per kg/ha applied N was 6.75 kg/ha grains. The genotype BRSMG Majestoso is the most responsive, with 14.4 kg/ha grains per kg applied N whereas the most tolerant is the MA-I-2.5 with1.8 kg/ha grains per kg N. Neste trabalho, objetivou-se verificar como ocorre o acúmulo de massa seca em linhagens de feijoeiro (Phaseolus vulgaris L.) diferindo na resposta ao fertilizante nitrogenado. Para isso, seis genótipos ('BRSMG Majestoso', 'Pérola', MA-I-18.13, 'Ouro Negro', 'BRSMG Talismã', MA-I-2.5) foram avaliados em Lavras, na presença de três níveis de N (0, 60 e 120 kg/ha), tendo como fonte de N o Sulfato de Amônio. O delineamento experimental foi o de blocos casualizados no esquema fatorial 6 x 3 com três repetições e as parcelas constituídas de cinco linhas de cinco metros. A semeadura foi realizada em novembro de 2005 e julho de 2006. Obteve-se, a partir de 35 dias após a semeadura, a massa seca total de cinco plantas competitivas, colhidas em local pré-determinado na área útil das parcelas. O processo repetiu-se a intervalos de 10 dias até à colheita. Avaliou-se também a produtividade de grãos em uma das linhas da área útil das parcelas. Constatou-se que no acúmulo de massa seca os genótipos não diferem na resposta aos níveis de N e o incremento médio por kg/ha de N aplicado é de 6,75 kg/ha de grãos. O genótipo BRSMG Majestoso é o mais responsivo, com 14,4 kg/ha de grãos por kg de N aplicado, e o mais tolerante é o MA-I-2.5 com 1,8 kg/ha de grãos por kg de N.